Establishing and Maintaining Wildlife Food Sources - Chris Demers; Alan Long; Chris Latt; Emma Willcox (EDIS)
Provide abundant and varied food sources for wildlife on your forested land, with this revised 5-page fact sheet written by Chris Demers, Alan Long, Chris Latt, and Emma Willcox, and published by the UF Department of School of Forest Resources and Conservation, May 2011. Reviewed 2014.